2022
DOI: 10.3389/fpls.2022.828287
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Chromosome Region Related to Melon (Cucumis melo L.) Fruit Surface Groove Trait Through Biparental Genetic Mapping and Genome-Wide Association Study

Abstract: The melon fruit surface groove (fsg) not only affects peel structure and causes stress-induced fruit cracking but also fits consumers’ requirements in different regions. In this study, genetic inheritance analysis of three F2 populations derived from six parental lines revealed that the fsg trait is controlled by a simple recessive inherited gene. Through bulked segregant analysis sequencing (BSA-seq), the Cmfsg locus was detected in an 8.96 Mb interval on chromosome 11 and then initially mapped to a region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In related research, a genetic study focusing on the fruit surface grooves in melon (Cucumis melo) identi ed the locus responsible on chromosome 11 (Zhao et al 2019). Subsequently, the gene MELO3C019694 encoding an AGAMOUS MADS-box transcription factor, was identi ed as being responsible for this trait (Du et al 2022). Previous studies highlighted the diverse regulatory roles of MADS-box family in fruit maturation, fruit skin development, and embryonic development in tomatoes (Busi et al 2003;Hileman et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In related research, a genetic study focusing on the fruit surface grooves in melon (Cucumis melo) identi ed the locus responsible on chromosome 11 (Zhao et al 2019). Subsequently, the gene MELO3C019694 encoding an AGAMOUS MADS-box transcription factor, was identi ed as being responsible for this trait (Du et al 2022). Previous studies highlighted the diverse regulatory roles of MADS-box family in fruit maturation, fruit skin development, and embryonic development in tomatoes (Busi et al 2003;Hileman et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (2018) found that overexpression of Malus domestica PISTILLATA causes vertical groove development on fruit from 12 days after pollination. Du et al (2022) identified a 1.07-kb deletion of a chromosome segment in groove lines of Cucumis melo and proposed that CmMADS-Box may be a candidate gene regulating the groove formation. It was also reported that certain Arabidopsis mutants with defects in the YABBY and SVP genes produced flowers with abnormal carpel fusions, which can possibly lead to groove-like structures (Nole-Wilson and Krizek, 2006; Gregis et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We searched the cucumber genome assemblies (9930v3.0 and Gy14v2.1; https://cucurbitgenomcs.org/, accessed on 1 April 2022) and there were 13 genes annotated as "Epidermal patterning factor-like protein", but none of them were located on cucumber Chr5. Similarly, the single gene (Cmfsg) for the fruit surface groove of melon was proposed to encode an AGAMOUS MADS-box transcription factor [16]. These observations suggest that the cucumber ribbing/nonribbing or melon fruit groove may have different genetic bases from fruit ridge continuity (CR/DCR) in bitter gourd.…”
Section: Discussionmentioning
confidence: 99%
“…In luffa, Luffa acutangula (L.) Roxb, the fruit ridge is also controlled by one major gene with partial dominance [ 15 ]. The ‘fruit surface groove’ described in melon ( Cucumis melo L.) is probably similar to fruit ridge, too; a simply inherited gene encoding an AGAMOUS MADS-box transcription factor was proposed to control this fruit skin feature [ 16 ]. Molecular mapping of fruit epidermal feature-related traits in bitter gourd is limited.…”
Section: Introductionmentioning
confidence: 99%